(untitled) (AYUSHDHARA, 2016)
Hair plays an important role in making body externally beautiful. Healthy and good looking long hair makes a person mentally enthusiastic and healthy. But in modern era due to extremely busy schedule, pollution and unhealthy diet, hair fall i.e. “Khalitya” is increasing day by day, and the main victims who are facing this problem are youngsters. Susceptibility of hair fall is more in males than in females. In Ayurvedic approach, falling of hair is coined out as in term of ‘Khalitya’. The medical term of baldness is alopecia; any type of hair loss is called alopecia. The aim of this article is to elaborate & explore the aetiology, patho-physiology & overall Ayurvedic treatment of Khalitya i.e., Nasya, Virechana, Leech therapy, Rasayana, Abhyang, different type of Lepa & Yoga. For Khalitya, Nasya is one of the best choices of management for its prime role in maintaining hair growth & preventing Khalitya. As per Ayurveda, ‘Khalitya’ (hairs fall) is a sign of ageing process and Rasayana therapy is paramount for ageing disorder. Massage (Abhyang) greatly improves the blood circulation, thus increasing the health of the hair & also scalp. Yoga like Sarvangasan increase blood flow toward brain. So we hope to get excellent result of Ayurveda in Khalitya.